Intake, metabolism parameters, and performance of growing beef cattle on pasture supplemented with different rumen undegradable protein with different amino acid profile - Camargo, K. D.V. [UNESP]; Messana, J. D. [UNESP]; Silva, L. G. [UNESP]; Granja-Salcedo, Y. T. [UNESP]; Dias, A. V.L. [UNESP]; Alves, K. L.G.C. [UNESP]; Gonçalves, P. H. [UNESP]; Souza, W. A. [UNESP]; Reis, R. A. [UNESP]; Berchielli, T. T. [UNESP] (Elsevier, 2022)
The aim of this study was to evaluate the effects of supplementation (3 g/kg BW) of RUP rumen undegradable protein (RUP) with different amino acid profile on the intake, rumen fermentation parameters, total-tract apparent digestibility, nitrogen balance, and performance of beef cattle grazing pasture in the rainy season. Two experiments were carried out simultaneously to evaluated intake and metabolism parameters (Exp.1) and animal performance (Exp.2). Exp.1 lasted 84 days and 9 castrated Nellore steers cannulated in the rumen and duodenum (18 ± 2 months old and 350 ± 78 kg initial BW) were assigned in 3 simultaneous 3 × 3 Latin squares design. Exp.2 lasted 112 days and 96 young Nellore bulls (12 ± 3 months old and 240 ± 19 kg initial BW) were assigned in a randomized block design. Animals were kept on pasture of Urochloa brizantha cv. Xaraés (CP = 12.3%), in continuous grazing and put and take method. The treatments were: 1) mineral supplementation (MS; ad libitum), 2) RUP supplementation with corn gluten meal 60 (CGM; 3 g/kg of body weight [BW] per day), and 3) RUP supplementation with protected soybean meal (PSBM; 3 g/kg of BW per day). The supplementation of RUP feed sources with different amino acid profile increased the intakes of DM supplement and CP, and the total-tract apparent digestibility of CP. In addition, animals supplemented with RUP, regardless the amino acid profile, had an increase in the excretion of N in feces and urine. However, both RUP supplementation increased final BW and total BW gain. The ADG of the animals was improved with an additional gain of 195 g/day for CGM and PSBM compared to MS, and no differences between RUP sources were observed. No differences in the intake of DM (kg and % of BW), OM, and forage DM, ruminal pH, and microbial-N across treatments. Animals supplemented PSBM had a greater NDF intake and total VFA concentration compared to CGM. Retaine-N (g/d) was increased by PSBM supplementation compared to MS, but it did not differ between RUP sources. Taken together, the results demonstrate that supplementation of 3 g/kg of BW of RUP with different amino acid profile during the rainy season is an effective nutritional strategy used to improve performance of growing beef cattle grazing pasture. In addition, RUP supplementation improved N metabolism, with PSBM resulting in greater N retained compared to MS supplementation.
Keywords: Amino acid; Body weight gain; Metabolizable protein; Nellore steer; Nitrogen retention